Developing Culture-Based English Instructional Materials to Improve Students’ Thinking, ELT Achievement, and Classroom Interaction - Zukhairatunniswah Prayati; Haerazi Haerazi; Lalu Ari Irawan; Rully May Vikasari (Lingua Cultura, 2020)
The research aimed to provide students’ learning and target needs of incorporating culture-based English instructionalmaterials in enhancing students’ critical thinking skills, ELT achievement, and classroom interaction at the Central Lombok middle schools. The research was a quantitative study. The 350 students and 10 English teachers were involved in the research. The average of students’ age ranged from 12-13 years old, while the English teachers were certified Englishteachers at the middle schools. They had also been from five to seven years of teaching practice experience. The data were collected using a questionnaire to see the students’ and teachers’ needs that were focused on target needs and learning needs. The target needs comprised the learning goals, lacks, and wants, while the learning needs included learning inputs, students’ roles, and classroom management. The data were analyzed using some steps; computation, display, drawing conclusion, and verification processes. Based on the data analysis, the target needs show that students are expected to get English proficiencies by providing them various cultural materials, namely local arts, traditional games, traditional rates, traditional technologies, and traditional pieces of literature. It can bring them to think critically to improve ELT achievement and build classroom interaction. At the same time, the analysis of learning needs informs that students need an appropriate English learning approach. They show they have an intention to be autonomous learners.